Dictatorship, magic and spell. The spiritual and sacred foundations of identity in the novels of Miguel Ángel Asturias - Garaczi, Imre (Acta Scientiarum Socialium, 2015)
Dictatorship, magic and spell. The spiritual and sacred foundations of identity in the novels of Miguel Ángel Asturias The Asturias novel portrays above all the traditional culture of the Central American country Guatemala in a modern 20th-century poetic approach. He was one of the few Latin American authors who have attempted to prevent the deliberate destruction of indigenous Amerindian cultures and who have drawn attention to the fact that Western capitalism is the accomplice of the dictatorial regimes prevalent in the Latin American countries known worldwide as „banana republics.” In this article, I will examine, through Asturias’ novels, the effects of „magic realism” on the identity-shaping of the South American nations.
Keywords: magic realism; identity; sacredness; spell; Latin American dictatorships; novel theory